Differences in Self-Directed Learning: Middle-School Students’ Autonomous Outdoor Studying - Uus, Õnne; Mettis, Kadri; Väljataga, Terje; Ley, Tobias (Frontiers in Education, 2021)
The use of self-directed learning (SDL) is an increasingly widespread trend in schools, although its core—the student’s attentional capability for multi-level processing—to construct relevant concepts and at the same time to keep in mind the needed sub-items, while also directing one’s own learning, has not been thoroughly investigated. We examined autonomous learning outdoors in small groups with 122 school students aged 14–16 years (the period that, through the developmental peculiarities of puberty, causes variety in cognitive skills). To detect whether individual characteristics reflect in students’ SDL progress, we measured participants’ pre-knowledge, their problem-solving strategies, and post-knowledge. We also asked about their prior SDL experience. The results showed 1) relations between one’s pre-and post-knowledge levels; 2) the impact of gender in the SDL efficacy; 3) the difficulty to memorize in the course of complex tasks while learning on one’s own. Our work gives insight into the SDL-specific heightened cognitive demand: school students’ cognitive obstacles in heavy load conditions and their prolonged maturation of executive functions—especially in adolescence as this age group passes its normal biological spurts of the human developmental path—which may differ individually.